Performance Appraisal Systems and Its Impact on Employee's Achievement in China’s Youmi Mobile - Bojun, Li; Saufi, Akhmad (Asian Journal of Applied Business and Management, 2024)
Performance appraisal systems are essential tools for aligning employee performance with organizational goals, and they play a particularly crucial role in rapidly growing sectors like China’s technology industry. This study explores the impact of performance appraisal systems on employee achievement at Youmi Mobile, a leading tech company in China, within the context of high-power distance and collectivist cultural norms. Using a quantitative research methodology, the study employed Structural Equation Modeling (SEM) to analyze data from 208 respondents across five key dimensions of performance appraisals: goal setting, performance evaluation, constructive feedback, development and career planning, and documentation. Findings reveal that all dimensions positively influence employee achievement, with development and career planning showing the strongest impact. These results suggest that culturally attuned performance appraisals can significantly boost employee productivity and satisfaction, offering valuable insights for HR practices in China’s tech sector. This research contributes to the broader understanding of performance management in Chinese corporate settings and provides a model for enhancing employee achievement through strategic appraisal systems.